Islam and the cyber world - Shuriye, Abdi Omar; Ajala, Mosud T. (Mediterranean Center of Social and Educational Research, 2014)
The mixed reactions on the use of the internet technology which have resulted in different debates and crimes in the cyber world calls for assessment of the Islamic point of view of the issue. Cyber world created avenue for the Muslim Ummah in a form of virtual global community and it encouraged dialogue as well as access to information on a real time basis; and above all facilitated easy access to the Qur’an. Nonetheless, th same tool has opened doors for crimes such as pornography, victimization, bullying, stalking etc. Hence this study reviews the benefits of the internet technology and consequences of its misuse. The frame of reference in measuring both the negative and positive aspects of this technology will be the Islamic standpoint.